Optimizing Warehouse Flow Through Lean Warehousing Method: Optimasi Aliran Gudang Melalui Metode Gudang Lean - Raihana Azahra Rusadi; Sumiati Sumiati (Academia Open, 2025)
General Background: Efficient warehouse management is crucial for sustaining competitiveness in manufacturing industries, where operational inefficiencies often lead to waste and reduced productivity. Specific Background: PT XYZ, a corrugated box manufacturer in Lamongan, faces persistent inefficiencies in its finished goods warehouse due to wasteful practices such as excessive searching, waiting, and product defects. Knowledge Gap: Despite the widespread application of Lean principles, limited studies have focused on integrating Lean Warehousing to systematically identify and eliminate multiple types of waste within Indonesian corrugated box manufacturing contexts. Aims: This research aims to analyze and reduce warehouse waste at PT XYZ using the Lean Warehousing approach to improve process flow and operational efficiency. Results: Through Value Stream Mapping, Process Activity Mapping, and Fishbone analysis, three critical wastes were identified—searching, defect, and waiting—addressed via FIFO implementation, inspection scheduling, and digitalized planning. The Process Cycle Efficiency (PCE) improved from 64.56% to 83.92%, with significant reductions in non-value-added time. Novelty: This study demonstrates a structured Lean Warehousing framework tailored for local manufacturing, integrating process mapping and digital enhancement. Implications: The findings provide a practical reference for industries seeking measurable waste reduction and productivity optimization through lean-based warehouse management strategies. Highlights: Identified key warehouse wastes: searching, defect, and waiting. Implemented Lean improvements raised PCE from 64.56% to 83.92%. Proposed digitalized planning and FIFO methods for sustained efficiency. Keywords: Lean Warehousing, Waste Reduction, Process Efficiency, Value Stream Mapping, Warehouse Optimization